Natural resource management for enhancing farmer's income: An optimal crop planning approach in Bihar - SINHA, D K; SINGH, K M; AHMAD, NASIM; CHAHAL, V P; MEENA, M S (The Indian Journal of Agricultural Sciences, 2018)
To maximize the income of farming community of the state and also to maintain the nutritional demand of an ever-increasing population, it is important to optimize the use of available land and water resources. An attempt has been made to revise the existing cropping pattern using linear programming considering land and groundwater as constraints. Data of Comprehensive Cost of Cultivation Scheme, Ministry of Agriculture and Farmers Welfare, GOI for the block year 2008-11 for Bihar was used to estimate the net returns at market price (MP), economic price (EP) and natural resource valuation (NRV) for obtaining an optimum crop plan. The optimal crop plan at existing groundwater use revealed the decline in gross cropped area (GCA) by -1.41% of existing GCA of the state. Few crops like paddy, wheat, ragi, sunflower and jute recorded declining trend in its area probably because of large water consuming crops. When groundwater use was increased by 25% of the existing GW use, the optimal crop plan indicated increase in GCA by 15.73% with respect to existing GCA. The level of profit would be earned more by 9% in optimum crop plan as compared to existing optimum crop plan. The optimum crop plan could be profitable and successful, when water development is further enhanced coupled with cheap source of irrigation facilities (electric and solar operated devices) made available to the farming community.